DEVELOPMENT OF UKRAINIAN INSTITUTE OF ADVOCACY IN THE SOVIET PERIOD IN THE ASPECT OF UNDERSTANDING THE EVOLUTION OF THE TERMS «LAWYER» AND «ADVOCACY» - V. V. Zaborovsky (Гуманитарные и юридические исследования)
The author explores the stage of development of Ukrainian institute of advocacy in 1917-1992, which was given the name of «Soviet» («post-revolutionary») period in the legal literature. The conclusion is that this period is characterized by a significant number of events which influenced the development of the national Institute of the Bar Association. The article notes that this period features the first reference to terms «lawyer» and «advocacy» in the legal acts, and the first cases to provide a legal definition of «advocacy». It is pointed out that during the period the legal profession was officially recognized by a constitutional body for the first time.